ANALISIS STRATEGI PELAYANAN PRA DAN PASCA BENCANA KEBAKARAN PADA DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN DI KABUPATEN SUMBAWA BARAT - SUMARTO, GATOT; ZULKIEFLIMANSYAH, ZULKIEFLIMANSYAH; UMAR, UMAR (Universitas Mahasaraswati K. Mataram, 2023)
Fire disasters occur due to excessive chemical reaction processes with oxygen and other substances such as carbon. In dealing with fire disasters, a fire prevention policy is needed to reduce the impact and occurrence of fire disasters. The purpose of this research is to determine the pre- and post-fire disaster service strategies carried out by the Fire and Rescue Service. The method used in this research is qualitative method. The data collection process uses observation, interviews and documentation. The results of this research are, 1) The West Sumbawa Regency fire and rescue service regarding the Pre and Post Fire Disaster Service Strategy has a work program in implementing its work strategy, 2) Factors that influence the Pre and Post Fire Disaster Service Strategy are infrastructure readiness and technological preparation , 3) Pre and Post Fire Disaster Service Strategy, namely the West Sumbawa Regency Fire and Rescue Service has an important role in efforts to prevent and prepare for fires